2011
DOI: 10.1016/j.juro.2011.03.099
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Inflammatory Bladder Disease: Cathelicidin Peptide Induced Bladder Inflammation and Treatment With Sulfated Polysaccharides

Abstract: Purpose Studies show that LL-37 is a naturally occurring urinary defensin peptide that is up-regulated during urinary tract infections. Although normal urinary LL-37 levels are antimicrobial, we propose that increased LL-37 may trigger bladder inflammation. We further suggest that anti-inflammatory sulfated polysaccharides known as semi-synthetic glycosaminoglycan ether compounds can treat/prevent LL-37 mediated bladder inflammation. Materials and Methods C57BL/6 mice were catheterized/instilled with LL-37 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 23 publications
3
48
0
1
Order By: Relevance
“…Following a challenge with 320 μM intravesical LL-37 (a concentration ~65 times greater than the minimal inhibitory concentration against UPEC), bladders from C57Bl/6 mice showed urothelial ulceration, oedema and increased inflammatory cell infiltrate. 65 In addition, lower concentrations of LL-37 (5-10 μM) were cytotoxic to the urothelium and induced urothelial apoptosis. 66 Thus, additional studies are needed to assess the cytotoxicity profile of LL-37, define its molecular and cellular mechanisms, and examine the epithelial and haematopoietic sources of its production during UTI.…”
Section: Cathelicidin Antimicrobial Peptidementioning
confidence: 99%
“…Following a challenge with 320 μM intravesical LL-37 (a concentration ~65 times greater than the minimal inhibitory concentration against UPEC), bladders from C57Bl/6 mice showed urothelial ulceration, oedema and increased inflammatory cell infiltrate. 65 In addition, lower concentrations of LL-37 (5-10 μM) were cytotoxic to the urothelium and induced urothelial apoptosis. 66 Thus, additional studies are needed to assess the cytotoxicity profile of LL-37, define its molecular and cellular mechanisms, and examine the epithelial and haematopoietic sources of its production during UTI.…”
Section: Cathelicidin Antimicrobial Peptidementioning
confidence: 99%
“…[20,32] The number of mast cells infiltrating into the tissue were quantified using a staining protocol for tryptase (rabbit anti-mast cell tryptase (1:800 dilution, Mast Cell Tryptase Antibody, sc-32889, Santa Cruz Biotechnology, Inc., Santa Cruz, CA, U.S.A.); biotinylated secondary antibody (1:2000 dilution, goat anti-rabbit IgG-B, sc-2040, Santa Cruz Biotechnology, Inc., Santa Cruz, CA); 3,3′-diaminobenzidine (DAB) peroxidase substrate). Five randomly selected high-power (400×) fields for each tissue were imaged, and the number of mast cells was quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Five randomly selected high-power (400×) fields for each tissue were imaged, and the number of mast cells was quantified. [20,32,41] The final results are presented as mast cell numbers per mm 2 sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing, it was also found that the intravesical instillation of cathelicidin, an antimicrobial peptide, and LL-37, C-terminal peptide fragment of the human cathelicidin, induces Hunner's lesions in the mucosa, acute inflammation, marked edema in all layers of the bladder and infiltration of polymorphonuclear leukocytes in healthy animal models (28). Other researchers also demonstrated that moderate stress, induced by exposing mice to constant illumination for 96 hours, resulted in desquamation of superficial and intermediate urothelial cells (29).…”
Section: Induced Ic Animal Models With Effects On Gags Depletion and mentioning
confidence: 96%